Companion Plant Reading - Astrid Møller-Olsen (Plant Perspectives)
Combining Donna Haraway’s call to acknowledge non-human significant others in her Companion Species Manifesto with the ‘biocentric form of literary criticism’11 Gagliano, Ryan and Vieira, ‘Introduction’, p. xi. advocated by critical plant studies, this essay uses the agricultural practice of companion planting as a Framework for reading beyond the canon of anglicised world literature. I analyse three short stories – Sofie Isager Ahl’s ‘Naboplanter’ (‘Companion Plants’, 2018), Can Xue’s ‘鸡仔的心愿’ (‘Chick’s Heart’s Desire’, 2020) and Audrey R. Hollis’ ‘Seedlings’ (2018) – that translate between the botanical and the human realms and use vegetal voices to challenge gendered social conventions, linguistic preconceptions and lingering anthropocentrism. By planting together texts in Chinese, Danish and English intermingled with the idiom of plants, I propose messy, multimodal and multilingual translation as a fundamental figuration in our pursuit of a planetary approach to comparative literature.